Святой доктор Федор Петрович: [роман] / Лев Копелев - Копелев Лев Зиновьевич (Соль Земли, 2013)
Экземпляры: Ф. 3 (20200710) / Инвентарный номер: 44246 / Цена: 170.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: К 65 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44